1993
DOI: 10.1103/physrevlett.70.3471
|View full text |Cite
|
Sign up to set email alerts
|

Unusual electronic structure ofPrBa2Cu3

Abstract: A model for the electronic structure of PrBa2Cu307 is proposed with three independent components: insulating CuC>2 planes with oxidation state Cu 11 , mixed valent Pr ions with almost equal numbers of Pr ,n and Pr IV , and CUO3 chains described by a t-J model with filling ^ 7. The difference from the high-r c superconductors comes from an enhanced stability of the Pr IV state due to the hybridization with O neighbors, and involves a transfer of holes from primarily planar O 2p a to 2p n states. The insulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
179
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 511 publications
(194 citation statements)
references
References 21 publications
15
179
0
Order By: Relevance
“…This type of hybridization is responsible for the suppression of superconductivity in 123 cuprates with Pr. 31 Hybridization of Bi 6s with O 2p orbitals has been shown to hinder the e g electrons mobility in bismuth-based manganites thus inducing charge order at very high temperatures in these systems ͓up to 600 K ͑Ref. 32͔͒.…”
Section: Discussionmentioning
confidence: 99%
“…This type of hybridization is responsible for the suppression of superconductivity in 123 cuprates with Pr. 31 Hybridization of Bi 6s with O 2p orbitals has been shown to hinder the e g electrons mobility in bismuth-based manganites thus inducing charge order at very high temperatures in these systems ͓up to 600 K ͑Ref. 32͔͒.…”
Section: Discussionmentioning
confidence: 99%
“…is both of fundamental and of practical interest. An unusual electronic structure of this compound was predicted [1,2]. According to these predictions, a strong hybridization of f-states in Pr with p-orbitals of 8 surrounding oxygens takes place [1].…”
Section: Study Of Transport In Prbagcu3_xmxo7_8mentioning
confidence: 99%
“…From these studies, it has been observed that increasing Pr substitution in RE 1−x Pr x Ba 2 Cu 3 O 7−δ , causes a monotonically decrease in the critical temperature (T C ) [6]. Some mechanisms such as hole localization [7,8], hole filling [9], magnetic pair breaking [10] and percolation [11] have been proposed to explain the degradation of superconductivity. Also, it was observed an ion-size effect in experiments on the RE 1−x Pr x Ba 2 Cu 3 O 7−δ system for RE = Nd, Eu, Gd, Y, Er and Yb, indicating an approximately linear T C decrease with increasing the RE-site ions radius for a fixed dopant amount x [12].…”
Section: Introductionmentioning
confidence: 99%